The rise of modern Japan - Beasley, W. G. (Weidenfeld and Nicolson, 1990)
The book went through several revisions and has been considered a standard work on its subject. When the author undertook yet another revision of the book in 1987, he discovered that he had altered his original volume to the extent that the new work, reviewed here, deserved a new title. Like its predecessor, this is a survey of modern Japanese history from its origins in the Tokugawa period to the present, bringing the story up through the death of Hirohito and the Recruit-Cosmos scandal in Japanese politics in the early part of 1989. While there is nothing astoundingly new in interpretation here, the book utilizes the most recent scholarship in the field and is good, solid history. Highly recommended for readers looking for a concise, well-written history of modern Japan.